Common Fixed Point Theorems for Weakly Contractions in Rectangular b-Metric Spaces with Supportive Applications. (13th January 2022) - Guan, Hongyan; Li, Jianju; Hao, Yan
Abstract : In this manuscript, two new classes of generalized weakly contractions are introduced and common fixed point results concerning the new contractions are proved in the context of rectangular b -metric spaces. Also, some examples are included to present the validity of our theorems. As an application, we provide the existence and uniqueness of solution of an integral equation.